2009
DOI: 10.1038/jid.2009.120
|View full text |Cite
|
Sign up to set email alerts
|

Ceragenins: A Class of Antiviral Compounds to Treat Orthopox Infections

Abstract: Eczema vaccinatum is a potentially fatal, disseminated viral skin infection that develops in individuals with atopic dermatitis after exposure to the vaccinia virus (VV). Despite advances in modern medicine, there are few options for those suffering from disseminated VV infections. Ceragenins (CSAs) are synthetic antimicrobial compounds designed to mimic the structure and function of endogenous antimicrobial peptides (AMPs). We show that CSA-13 exhibits potent antiviral activity against VV by (1) direct antivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 31 publications
0
44
0
4
Order By: Relevance
“…Topical administration of CSA-13 on vaccinia-inoculated mice resulted in a significant decrease in the number of satellite lesions, and preincubation of the virus with CSA-13 inhibited viral replication. Notably, in these studies, Howell et al [51] observed that treatment of human keratinocytes with CSA-13 induced LL-37 and beta-defensin 3 production.…”
Section: Mechanism Of Actionmentioning
confidence: 96%
See 2 more Smart Citations
“…Topical administration of CSA-13 on vaccinia-inoculated mice resulted in a significant decrease in the number of satellite lesions, and preincubation of the virus with CSA-13 inhibited viral replication. Notably, in these studies, Howell et al [51] observed that treatment of human keratinocytes with CSA-13 induced LL-37 and beta-defensin 3 production.…”
Section: Mechanism Of Actionmentioning
confidence: 96%
“…The activities of AMPs against lipid-enveloped viruses has been well established, but a full description of their antiviral activities has not been realized [49,50]. Howell et al [51] studied the activities of ceragenins against vaccinia virus. They showed that CSA-13, at a concentration comparable to the human AMP, LL-37, caused viral disruption.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are characterized by a broad spectrum of bactericidal activities against viruses, Gram-negative and Gram-positive bacteria (3)(4)(5), fungi, and parasites (6). Like that of natural CAPs, the bactericidal activity of ceragenins declines in the presence of blood plasma; the development of ceragenins is currently directed to topical applications (7)(8)(9).…”
mentioning
confidence: 99%
“…Significant activity of CSA-13 against cariogenic and periodontopathic bacteria correlate with its ability to bind bacteria lipopolysaccharide and lipoteichoic acid linked to erythrocytes [30]. CSA-13 is also active against vaccinia virus (VV) [31] and Trypanosoma cruzi [32]. Although some forms of ceragenins are effective against both Gram-negative and Gram-positive bacteria, they are generally more potent against Gram-positive bacteria (Figures 1 C and 1 D).…”
Section: Cerageninsmentioning
confidence: 99%